SOSIALISASI KESELAMATAN KERJA TERHADAP PENURUNAN KEJADIAN KECELAKAAN KERJA DI PUSKESMAS KLARI KARAWANG - Jumaedi, Jumaedi; Darmawan, Wendi; Yuliana, Chaerani Tri; Muhidin, Muhidin; Widhiantika, Wieke (LP2M STP Mataram, 2023)
Occupational health and safety (OHS) is a crucial aspect of protecting workers from the risks of accidents and work-related illnesses, especially in healthcare facilities such as community health centers (Puskesmas). This study aims to evaluate the impact of a safety training program on reducing the number of workplace accidents at Puskesmas Klari Karawang. This community service program was implemented through several stages, including problem identification, material preparation, initial outreach, training and simulations, interactive discussions, and ongoing monitoring and evaluation. The results show a significant reduction in workplace accidents across all categories. Minor accidents decreased by 40%, moderate accidents by 46.7%, and severe accidents by 60%. This decrease was influenced by an increase in workers' knowledge and compliance with the use of personal protective equipment (PPE) and the implementation of safety protocols. Furthermore, continuous monitoring and evaluation confirmed the program’s effectiveness in fostering a stronger safety culture within the workplace. This occupational safety outreach program has demonstrated positive outcomes in reducing workplace accidents and can be adapted by other healthcare facilities